Revitalizing culture and ecosystems through environmental education in Samburu, Kenya - Trimarco, Jon, author (Colorado State University. Libraries, 2015)
Traditional ecological knowledge (TEK) is being lost across the planet and it is feared that, as a consequence, indigenous communities have become less resilient in the face of environmental changes. In this talk, Jon will reflect on his experiences leading a collaborative effort to address such concerns among the pastoralists of Samburu, Kenya. Through a fellowship with the CCC, Jon and his team investigated the nature of TEK loss in Samburu, created TEK-centered environmental education programs and mobilized hundreds of community members in afforestation efforts using both traditional and western techniques. This talk will focus on the importance of collaboration in developing environmental education programs and the surprising 'innovations' that can be discovered while working with TEK.
Presented at the Spring 2015 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series highlights the work of the Cohort 6 Fellows. Series Spring 2015 presents: Jon Trimarco, February 10th, 2015, Colorado State University, Fort Collins, Colorado.
Jon Trimarco is currently pursuing his masters in the department of Human Dimensions of Natural Resources. For his thesis he is investigating the relationship between Kenya's formal education system and the rate of traditional ecological knowledge erosion in Samburu, Kenya, where he has spent the past two field seasons. He recently served as a Peace Corps volunteer in Ghana, working as an agroforestry extensionist and environmental educator. He is an alumni of the Warner College, with a bachelors in Conservation Biology.
PowerPoint presentation.